Chlorpyrifos Biodegradation in Laboratory Soil Through Bio-Augmentation and Its Kinetics - Farhan, Muhammad; U. Khan, Amin.; Wahid, Abdul; Ahmad, Maqsood; Ahmad, Farooq; Ali Butt, Zahid; Kanwal, Amina (Asian Journal of Chemistry, 2013)
The consumption of pesticides is increasing at an alarming rate in the third world countries including Pakistan and is creating serious environmental and health concerns. Pesticides are often persistent in soils and reach to humans by entering into food chain. Biostimulation and bioaugmentation are considered as most reliable techniques for pesticide remediation, being eco-friendly. The present study deals with the biodegradation of chlorpyrifos in soil. Selected isolate of previous study were tested in soil to explore in situ bioremediation possibilities. It was noted that the strain which was potent in liquid media also showed good result in soil. The degradation percentage was 84 by Klebsiella sp. Enhancement potential of different organic amendments was studied and the results revealed that farmyard manure has most enhancing effect. Lastly, the biodegradation kinetics in soil was calculated. The kinetic data revealed that Klebsiella sp. have the potential for bioremediation and can be used for rapid chlorphyrifos degradation. The present study was thus innovative and successful in providing the eco-friendly solution using indigenous bacteria for countering chlorphyrifos pollution. This strain can be used for soil and ecological restoration.